Pengaruh Lokasi Kualitas Produk, Kualitas Pelayanan Dan Harga Terhadap Keputusan Pembelian Pada Bingsoo Café Kota Malang - Suryawan, Zarkasih; Basalamah, Muhammad Ridwan; Rahmawati, Rahmawati (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This research aims to determine and analyze the influence of: 1. Location on purchasing decisions. 2. Product Quality on Purchasing Decisions. 3. Service Quality and Price on Purchasing Decisions. The sampling technique used is a non- probability sampling technique, namely Accidental Sampling, which is a sampling method that is in accordance with the criteria in the research. This sample was determined using the Malhotra formula and data was obtained for 100 samples. The data analysis method used here is Multiple Linear Regression Analysis. It can be concluded that price has a negative and significant effect on purchasing decisions and product quality has a significant positive effect on purchasing decisions  Keywords: Buying Decision, Location, Product Quality, Service Quality, Price